Use of a mouse model for the isolation of Borrelia puertoricensis from soft ticks - Edwin Vázquez-Guerrero; Alexander R. Kneubehl; Guadalupe C. Reyes-Solís; Carlos Machain-Williams; Aparna Krishnavajhala; Paulina Estrada-de los Santos; Job E. Lopez; José Antonio Ibarra (PLoS ONE, 2025)
The isolation of tick-borne relapsing fever (TBRF) spirochetes has proven to be a useful tool to understand their distribution in geographic areas where the tick vectors inhabit. However, their isolation and culture are not easy and in general an animal model is needed to achieve this task. Here, argasid ticks were collected from a neighborhood in Ciudad Caucel, and they were identified as Ornithodoros (Alectorobius) puertoricensis. To determine whether these were infected with TBRF bacteria they were fed with healthy mice but only a low burden of spirochetes was observed. An immunosuppressed mouse model was used to feed the ticks suspected to be infected with spirochetes. After tick feeding, a higher number of bacteria was observed in blood samples, and spirochetes were successfully cultivated in Barbour-Stoenner-Kelly (BSK)-IIB media. Molecular analyses indicated that the isolate was Borrelia puertoricensis, while whole genome sequencing confirmed the finding. In summary, the present report shows that A. puertoricensis is present in Ciudad Caucel, an urban neighborhood in the outskirts of Merida city, and these ticks are infected with B. puertoricensis. Despite the fact that this species has not been directly associated with TBRF it represents a potential medical and veterinary health risk.